Measurement properties and feasibility of the Loughborough soccer passing test: A systematic review - Wen, D.; Robertson, S.; Hu, G.; Song, B.; Chen, H. (Journal of Sports Sciences, 2018)
The purpose of this paper was to systematically review the literature and examine the research methodological quality, measurement properties and feasibility of the Loughborough Soccer Passing Test (LSPT). Databases were searched up to June 2017. Twenty five studies fulfilled the eligibility criteria. The main methodological limitations of the studies were the small sample size and the lack of information on participants and eligibility criteria. Results showed that test-retest reliability of the LSPT was moderate to excellent. Good discriminative validity was found between playing levels and ages. The LSPT was positively correlated with sprint, dribbling, and agility test; however, a weak correlation was established with in-game performance. Test responsiveness (an ability to detect change over time) to some external interventions was observed in studies. Adjusted Cronbach`s alpha (a = 0.67), smallest worthwhile change (SWC = 0.8-3.8) and minimal detectable change (MDC50 = 1.9-11.3) were calculated based on available data. The findings indicate that the LSPT has acceptable test-retest reliability and discriminative validity. However, it may not be a feasible and effective way to interpret the intra-individual change of skill performance in practice. Future work should be undertaken to establish additional measurement properties of the LSPT, and to improve its practical feasibility.